An implementation strategy package (video education, HIV self-testing, and co-location) improves PrEP implementation for pregnant women in antenatal care clinics in western Kenya - Joseph Sila; Anjuli D. Wagner; Felix Abuna; Julia C. Dettinger; Ben Odhiambo; Nancy Ngumbau; George Oketch; Enock Sifuna; Laurén Gómez; Sarah Hicks; Grace John-Stewart; Grace John-Stewart; et al. (Frontiers in Reproductive Health, 2023)
BackgroundPre-exposure prophylaxis (PrEP) is recommended by the World Health Organization and the Kenyan Ministry of Health for HIV prevention in pregnancy and postpartum for women at risk for HIV. Integration of PrEP into antenatal care is promising, but delivery gaps exist in the face of healthcare provider shortages in resource-limited settings.MethodsBetween May and November 2021, we conducted a difference-in-differences study (3 months pre-intervention data collection and 3 months post-intervention data collection) analyzing four intervention facilities, where the strategies were implemented, and four comparison facilities, where no strategies were implemented. We tested a combination of three implementation strategies—video-based PrEP information in the waiting bay, HIV self-testing, and dispensing of PrEP in the antenatal care rooms—to improve PrEP delivery. We compared absolute changes in the proportion of antenatal attendees screened for PrEP (PrEP penetration), the proportion receiving all PrEP-specific steps in a visit (HIV testing, risk screening, and PrEP counseling) (PrEP fidelity), and client PrEP knowledge, client satisfaction, and waiting time and service time (a priori outcomes); post hoc, we compared the proportion offered PrEP (PrEP offer) and completing HIV testing. We measured provider perceptions of the acceptability and appropriateness of the implementation strategies.ResultsWe observed significant improvements in PrEP penetration, PrEP offer, satisfaction, and knowledge (p < 0.05) and improvements in fidelity that trended towards significance (p = 0.057). PrEP penetration increased 5 percentage points (p = 0.008), PrEP fidelity increased 8 percentage points (p = 0.057), and PrEP offer increased 4 percentage points (p = 0.003) in intervention vs. comparison facilities. Client PrEP knowledge increased by 1.7 out of 6 total points (p < 0.001) and client satisfaction increased by 0.7 out of 24 total points (p = 0.003) in intervention vs. comparison facilities. We observed no changes in service time (0.09-min decrease; p = 0.435) and a small increase in waiting time (0.33-min increase; p = 0.005). HIV testing among those eligible did not change (1.5 percentage point decrease, p = 0.800). Providers felt the implementation strategies were acceptable and appropriate (median acceptability: 20/20; median appropriateness: 19.5/20). However, absolute levels of each step of the PrEP cascade remained suboptimal.ConclusionsAn implementation strategy package with video information, HIV self-testing, and co-location of medication dispensing enhanced PrEP delivery across several implementation outcomes and client satisfaction, while not substantially increasing wait time or decreasing provider-client contact time.Clinical trial registrationClinicalTrials.gov, identifier, NCT04712994.